On a Subclass of Multivalent Functions with Bounded Positive Real Part - Ganapathi, Thirupathi (International Journal of Advanced Mathematical Sciences, 2019)
In the present paper, by introducing a new subclass of multivalent functions with respect to - symmetric points, we have obtained the integral representations and conditions for starlikeness using differential subordination.